2018
DOI: 10.1130/g40187.1
|View full text |Cite
|
Sign up to set email alerts
|

Centennial-scale dynamics of the Southern Hemisphere Westerly Winds across the Drake Passage over the past two millennia

Abstract: This supplementary file includes 1. Site information 2. Age-depth model and loss-on-ignition results from core PAT16-AP1 3. Macrofossil analysis results from core PAT16-AP1 4. Evaluation of evaporative effect on oxygen isotopes of moss cellulose 5. Air-parcel backward trajectory analysis using HYSPLIT model 6. A close-up look of PAT16-AP1 proxy record for the last 150 years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…Links between SHW, temperature, and rainfall. Links between SHW, temperature and rainfall are well established in recent regional meterological 23,48,49 and paleoclimate records 32,33,[50][51][52] . While not universal (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Links between SHW, temperature, and rainfall. Links between SHW, temperature and rainfall are well established in recent regional meterological 23,48,49 and paleoclimate records 32,33,[50][51][52] . While not universal (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…6) that is not observed farther north in the rest of Patagonia. Independent paleoclimate proxies provide evidence for enhanced westerly flow and Pacific-derived moisture over Tierra del Fuego from ∼1000 to ∼700 yr ago (Xia et al, 2018;Fig. 5), as well as wetter conditions in eastern Tierra del Fuego (Björck et al, 2012).…”
Section: The Last Millennium and Dendroglaciologymentioning
confidence: 99%
“…On the other hand, the tidewater Marinelli and Pia glacier (Kuylenstierna et al, 1996;Strelin et al, 2008;Hall et al, 2019;Meier et al, 2019;Menounos et al, 2020), along with a reconstruction of moisture provenance in Tierra del Fuego using sphagnum cellulose δ 18 O (Xia et al, 2018), a precipitation reconstruction farther east from Isla del Estado (54.8°S, 64.4°W; Björck et al, 2012), and a southern Patagonian record of nonarboreal pollen slightly farther north at ∼50°S, a proposed proxy for varying Holocene Southern Annular Mode (SAM)-like conditions (Moreno et al, 2018). Periods of inferred westerly intensification over Tierra del Fuego, per Xia et al (2018), are indicated by vertical pink shading. 10 Be ages are also plotted, including inferred outliers.…”
Section: Late Holocene Glacier Maximummentioning
confidence: 99%
“…In addition, wind proxy records from sub-Antarctic Macquarie Island 50 (Fig. 3g) and southernmost Patagonia 51 suggest a significant poleward displacement and likely intensification of westerlies ~A.D. 1700, when glacial discharge at site PS67/182-1 increases beyond the long-term mean (Fig.…”
Section: Resultsmentioning
confidence: 99%